Measuring Text-Focused Reading Instruction - Cohen, Julie; Chung, Rosalie; Miller, Luke C.; Ruzek, Erik; Wiseman, Emily (Journal of Education, 2024)
Helping students engage with complex texts has been a longstanding challenge, though teachers have received little guidance about practices that help students in engaging with texts. This paper provides a range of empirical evidence about a tool designed to provide formative insight into text-focused teaching, which we used to reliably score more than 500 reading lessons in a large district. We describe the structure of the tool, its relationship to other measures of teaching, teacher and school attributes, and student outcomes. We then provide guidance to practitioners and researchers seeking to employ such a tool for teacher development.
Keywords: Achievement; Classroom; Educational Studies; Teaching; Literacy